Journalism, medias and Heritage: from the Archaeological and Paleontological curiosity to Science and regional development - Meneses Fernández, Mª Dolores (Estudios sobre el Mensaje Periodístico, 2012)
Cultural heritage, its care and enjoyment by successive generations are indication of social development. Journalists and researchers or managers of archaeological and paleontological heritage have begun a fruitful mutual collaboration without return. It is a new framework that aims to strengthen the presence of cultural heritage in the media. In this paper the author propose a guideline in order to optimize the relationship between media managers, journalist, archaeologist and paleontologist.
Keywords: Specialized Journalism; Social Communication of Science; Archaeological Heritage; Paleontological Heritage.